2011
DOI: 10.1143/jjap.50.01bc12
|View full text |Cite
|
Sign up to set email alerts
|

Double-Faced Organic Light-Emitting Device Using Laminate Method

Abstract: A scenario for stabilization of axionic moduli fields in the context of type IIB Calabi-Yau flux compactifications is discussed in detail. We consider the case of a Calabi-Yau orientifold with h 1,1 − = 0 which allows for the presence of B 2 and C 2 -moduli. In an attempt to generalize the KKLT and the Large Volume Scenario, we show that these axions can also be stabilized -some already at tree level, and others when we include perturbative α ′ -corrections to the Kähler potential K and nonperturbative D3-inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…[127] Other techniques use lamination or laser transfer techniques to deposit the top electrode, which allows for monolayer functionalization as described above. [144,145] Interface Electrical Dipole Layers in OPVs…”
Section: Potential Shifts At Electrode Interface Layersmentioning
confidence: 99%
“…[127] Other techniques use lamination or laser transfer techniques to deposit the top electrode, which allows for monolayer functionalization as described above. [144,145] Interface Electrical Dipole Layers in OPVs…”
Section: Potential Shifts At Electrode Interface Layersmentioning
confidence: 99%
“…As a deposition technology for the solution process, roll-to-roll coating [1], slit coating [2], and spin coating [8] have attracted significant attention. On the other hand, lamination has garnered interest as an encapsulation technology, and many lamination methods have been proposed [9][10][11][12][13][14][15]. The lamination history began with Yang et al's report [9] in 2001 for double-substrate technology and Rogers et al's report [10] in 2004 for single-substrate technology.…”
Section: Introductionmentioning
confidence: 99%
“…Duggal et al reported OLEDs fabricated using a vacuum-free, direct lamination process of two PET substrates [14]. Naka et al proposed a double-faced transparent OLED made using the lamination method [15]. Several studies have also been conducted on the interfacial properties of laminated polymer diodes in chemical and mechanical aspects [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We have been focusing on the lamination process [17][18][19][20][21], which is wet process compatible, for PLED fabrication. The laminated PLEDs are formed by laminating two substrates.…”
Section: Introductionmentioning
confidence: 99%